ON THE ISSUE OF JURIDICAL CONSTRUCTION OF CONSENSUAL AND REAL CONTRACT - Y. A. Serkova (Russian Journal of Economics and Law)
Objective: to reveal the essence of consensual and real contracts as juridical constructions. Methods: historical-legal, formal-juridical and comparative-juridical. Results: using the methodological properties of “juridical construction” category, the author has compared the real and consensual deals, analyzed the legal nature of property alienation and its significance for civil contract. Scientific novelty: the author reveals and grounds the principle of unity and differentiation in interaction of a contract as a juridical fact and a contractual legal relationship as elements of juridical construction of civil-legal contract. Practical value: possibility to use the research results in law enforcement activity and contract practice.